Hatchetations: Carry A Nation’s Sober Defense for Kansas - Peterson, Sarah A. (My University, 2016)
In 1904, the infamous, hatchet-wielding prohibitionist Carry A. Nation published her autobiography with the humble title The Use and Need of the Life of Carry A. Nation. The book, printed by F. M. Steves & Sons of Topeka in 1904, stands as a bookish monument to Midwestern patriotism. Bound in a rich sunflower-colored cloth, the book spells out its title in sparkling golden letters. The bright yellow binding showcases Nation’s love for Kansas, the Sunflower State. In the frontispiece, you see Nation for once without her hatchet leaning over her Bible. Nation believed that God had called her to rally against the evils of alcoholism and to physically smash saloons. In fact, the almost six-feet-tall Nation liked to preface her destructive raids or “hatchetations,” as she came to call them, with the exclamation: “Men, I have come to save you from a drunkard’s fate.” In the autobiography, Nation recalls her baptism by the Holy Ghost alongside frequent metaphysical visitations. “God showed me in a vision two men crouched on each side of the door ready to either catch or slug me,” she testifies, “if the door was opened.” Nation’s mother Mary Moore, who believed for a time that she was Queen Victoria, was found to be of “unsound mind” by a jury in 1890. Carry A. Nation, whose first husband Charles Gloyd died in 1869 of alcoholism, however, turned out to be a highly effective leader of the Woman’s Christian Temperance Union (WCTU). After moving with her second husband, David Nation, from Texas to Kansas in 1889, she opened a local chapter of the WCTU in Barber County and became a mouthpiece for many Kansas women, who witnessed alcohol destroy their families and communities. Between 1900 and 1920, Nation was arrested over 30 times for her hatchetations, yet she managed to pay jail fines from her lecture-tour fees and the sales of souvenir hatchets, the curious symbol that shaped her public perception as a half-crazed domestic “home-defender.”